CURRENT STATE OF EXTERNAL MIGRATION CAUSED BY RUSSIA-UKRAINE WAR - Ishchuk, Andrii (Collection of scientific papers «ΛΌГOΣ», 2023)
The aggressive military actions taken by Russia against Ukraine have had disastrous consequences, resulting in extensive destruction and immense suffering for the Ukrainian population. The conflict in Ukraine has caused a massive migration of the population, with many having to leave their homes. This has resulted in some moving to other parts of the country, while others have had to seek refuge abroad. Some have already returned to their original homes, while others may still have to consider leaving in the future. This sudden change of residence has created new difficulties, both for the host communities and for the ones that people are leaving. The effects and implications of relocation must be taken into consideration when formulating national and local strategies.